2018
DOI: 10.3174/ajnr.a5793
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Blood Velocity with 4D Digital Subtraction Angiography Using the Shifted Least-Squares Method

Abstract: The availability of 4D-DSA provides the opportunity to use the shifted least-squares method to estimate velocity in vessels within a 3D volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Wu et al 25 applied a shifted least-squares analysis to time curves in a given phantom vessel segment. The vessel centerline and radii of each vessel segment of interest were determined at discrete intervals, and TDCs were recorded.…”
Section: Clinical Applications Of 4d-dsamentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al 25 applied a shifted least-squares analysis to time curves in a given phantom vessel segment. The vessel centerline and radii of each vessel segment of interest were determined at discrete intervals, and TDCs were recorded.…”
Section: Clinical Applications Of 4d-dsamentioning
confidence: 99%
“…A velocity for the segment was determined from temporal shift and spatial distance information with a relative root-mean-square error of 11% and a Pearson correlation coefficient with phase contrast (PC)-MR imaging of r ¼ 0.835. 25 Shaughnessy et al 26 derived a similar shift from the phase signal in the Fourier domain to determine liquid velocities in a given 3D-printed, patient-specific vessel segment. In each vessel segment, the vessel centerline, discrete distances, and radii were determined.…”
Section: Clinical Applications Of 4d-dsamentioning
confidence: 99%
“…Quantitative angiographic techniques, including quantitative color-coded DSA, 4D DSA, 4D Flow MR and 4D transcatheter perfusion, can provide data on hemodynamic parameters (e.g. time of arrival, flow, velocity) (Meram et al 2019 ; Shaughnessy et al 2018 ; Wu et al 2018 ; Motoyama et al 2017 ; Nett et al 2012 ; Frydrychowicz et al 2011 ; Wang et al 2010 ; Gu et al 2005 ). The application of MRI techniques for real-time guidance is limited by the need for additional specialized equipment and suites.…”
Section: Introductionmentioning
confidence: 99%
“…4D-DSA provides both the temporal and spatial information required to calculate velocity and flow. [8][9][10] The velocity and flow calculations depend on the following: 1) visualizing the cardiac-induced rhythmic changes in contrast bolus density occurring between systole and diastole, 2) quantifying the arrival time of the time-varying bolus between 2 points along a vessel, and 3) quantifying the vessel cross-sectional area. The method exploits a naturally occurring image signal in 4D-DSA acquired with arterial injection.…”
mentioning
confidence: 99%
“…Studies documenting the feasibility of using the data from a 4D-DSA reconstruction to quantify velocity and flow were recently published by Shaughnessy et al 8 and by Wu et al 9 In both reports, calculation of velocity and flow was found to be dependent on accurate identification of a pulsatility signal in the time-density curves (TDCs) of a reconstruction; this requirement was noted to be a potential limitation of both methods used for quantification. The pulsatility signal is defined as the change in bolus density between systole and diastole as seen in a TDC for a given point in the volume as a function of time.…”
mentioning
confidence: 99%